PENGEMBANGAN PERANGKAT PENILAIAN OTENTIK PADA MATA KULIAH KULTUR JARINGAN - Khairina Afni (Jurnal Pelita Pendidikan, 2016)
This research was conducted aiming to find out the quality, appropriateness and effectiveness of authentic assessment tool developed in tissue culture courses. This research was conducted in the Department of Biology Education Faculty of Mathematics and  Natural Sciences (FMIPA) UNIMED in January-June 2014, by using the development model of Borg and Gall. This development research generally can be grouped into three procedures, the first phase is the product development model by conducting a needs analysis through the analysis of the material, standard competencies and tasks, the second phase is the procedure of design product, developmentproduct, validation assessment by a team of experts, and the third phase is to test the product that includes the trials of individuals test, small groups and large groups. The resulting product was an authentic assessment tool that used by students of Biology education semester VIII force 2010 UNIMED. Authentic assessment tool compiled and assessed by a team of qualified validation. The results of the assessment team of experts the material showed an average 86% category was excellent, and expert design assessment was 95% with a very good category. Individual testwas 77% with the criteria very  well. A small group test was 82% with very good criteria, testing a large group test was 89% by category is very good. Feasibility product test was 89% with a very worthy category and the test of the effectivity in authentic essessment tool and 42 students of eighth semester of biology education UNIMED assessed  89% effectivity Authentic Assessment Tool development in tissue culture Courses this very well.